The Influence of Digital Engagement and FOMO on the Intention to Participate in Community Based Running Events - Kayla Diandra Alisya; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study investigates the influence of digital engagement and the Fear of Missing Out (FOMO) on individuals’ intention to participate in community-based running events. As digital platforms increasingly shape how runners connect, share experiences, and follow community activities, understanding their behavioral impact becomes essential. Using a quantitative approach, data were collected through an online questionnaire distributed to active and potential members of running communities and analyzed using PLS-SEM. The results show that both digital engagement and FOMO significantly and positively affect participation intention, with digital engagement also acting as a partial mediator that strengthens the effect of FOMO. These findings highlight how interactive digital content and social exposure play a vital role in encouraging physical event participation. The study contributes to the literature on sports participation behavior in the digital era and offers practical insights for organizers and sports marketers to optimize digital strategies, enhance community connection, and design more compelling communication to increase event participation.